Analisis Kejahatan Yang Berkembang Dalam Masyarakat Desa Banuasibohou 1, Kecamatan Alasa - Waruwu, Firdamai Yanti; Hulu, Pergawan Canofan; Harefa, Hendrikus Otniel Nasozaro (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study examines the phenomenon of the increasing incidence of minor crimes in Banuasibohou 1 Village, Alasa Subdistrict, North Nias Regency, with a primary focus on its connection to drunken behavior resulting from the consumption of local alcoholic beverages. This issue has become a serious concern, as it not only disrupts public order but also undermines the cultural and traditional values long upheld by the Nias community. The aim of this research is to determine the extent to which the intensity of alcohol consumption contributes to the rise in criminal behavior within the village environment, as well as to understand the social and cultural roots of such behavior. The study was conducted using a mixed-methods approach, involving interviews, field observations, and quantitative surveys to test the hypothesis regarding the relationship between drunkenness and crime.